PERAN MUSYAWARAH DESA DALAM PENGELOLAAN KEUANGAN DESA (Studi Kasus Pelaksanaan Musyawarah Desa di Desa Penidon Kecamatan Plumpang Kabupaten Tuban - Rachadian, Tezar; Sulistyaningsih, Endang (Kajian Hasil Penelitian Hukum, 2023)
The aim of this study was to determine the form of accountability of the Penidon Village government in managing village finances and the role of the Village Consultative Body (BPD) as a representative of villagers in supervising village financial management. As well as to find out the role of the Village Deliberation Forum (FMD) in managing village finances, so that the risk of legal problems can be minimized. The research location is in Penidon Village, Plumpang District, Tuban Regency. This research use qualitative descriptive research method which interview results as a primary data and a literature review related to the research material as secondary data.  As a result : (1) Accountability problems for financial management in Penidon Village for the 2014 to 2015 Fiscal Year. The ro le of the BPD (Village Consultative Body) in supervising financial management was not optimal because of the low level of awareness and legal compliance of village financial managers in that period , as well as a lack of understanding of the latest legal developments. (2) The role of the Village Deliberation Forum (FMD) in the financial management of Penidon Village for the 2014 up to 2023 Fiscal Year is still not maximized. During this period, the Penidon Village meeting was only used once in early 2023 to resolve village financial management issues, the rest of the village financial management issues were resolved through prosecution by Law Enforcement Officials (APH). This is because the laws and regulations do not specifically regulate the role of the Village Consultative Council in Village Financial Management, as well as in resolving village financial management problems. To overcome these problems, the following can be done: (1) Improving the implementation of village government accountability and maximizing the role of the Village Consultative Body in managing village finances, increasing legal awareness of the community in general and village management parties in particular; (2) Optimizing the Village Deliberation Forum (FMD) to create accountable village financial management, which can be done by expanding the role of FMD in village financial management using a responsive legal perspective, namely responding to community wishes and being committed to achieving substantive justice; (3) In addition, regional heads can request outreach, guidance and consultancy to the Financial and Development Supervisory Agency (BPKP) regarding the implementation of an internal control system for village financial management in their area.